Mexican Politeness: an Empirical Study on the Reasons Underlying/Motivating Practices to Construct Local Interpersonal Relationships - Gerrard Mugford (Russian Journal of Linguistics, 2020)
Fundamental concepts are all too often taken for granted in im/politeness research, especially since they are not always carefully and fully defined before researchers engage in confronting methodological issues. Definitions of im/politeness may reflect ‘armchair’ or intuitive approaches (Jucker and Staley 2017), which frequently ignore the sociocultural context within which relational work is performed. Following Larina’s (2015) concept of communicative ethno-style , this study examines how Mexican im/politeness studies regularly build on classic ethnocentric decontextualised im/politeness approaches (e.g., Brown and Levinson 1987) and fail to understand laypeople’s co-constructed discursive approaches (e.g. Watts 2003). This paper questions national and regional stereotypical approaches to understanding im/politeness practices and patterns. It examines the Mexican context and identifies how relational work is carried out at a localised level. Individual interactants can decide how they want to come across and which pragmatic resources they will employ when constructing, developing and maintaining interpersonal relationships. The paper is structured in the following way. First, I examine theoretical, discursive and contextually explanatory approaches to researching Spanish-language im/politeness in general. Then, by focusing on individual underlying social and linguistic behaviour, I scrutinise particular Mexican sociocultural politeness practices such as displaying confianza (familiar trust) and respeto (hierarchical respect) (Félix-Brasdefer 2008). In order to do so, I asked interview participants to assess their own motivations behind employing such im/politeness practices and provide experiences/instances of Mexican sociocultural practices. Finally, discussion focuses on how Mexican interactants co-construct interpersonal relations and how these are reflected through localised im/politeness patterns and practices